IMPLEMENTASI PERANCANGAN SISTEM ABSENSI KARYAWAN MENGGUNAKAN LOCATION BASED SERVICE BERBASIS ANDROID - Sinaga, Dini; Nopriadi (Computer Science and Industrial Engineering, 2024)
Technological developments affect all aspects of both the world of education and companies. Many companies have used mobile to help with all activities because mobile is connected to the internet and can access quickly anywhere and at any time. Android is a Linux-based operating system that can be used on various mobile devices. PT. Amtek Engineering carries out employee attendance using a magnetic card machine. Basically there are no problems with taking attendance using a magnetic card machine, it's just that machine errors often occur, such as the in/out slot number which causes the employee not to be registered for incoming or outgoing attendance, which can be detrimental to the employee, besides using a card slot. can cause long queues so that employee attendance often becomes late and employee salaries are cut. Therefore, a computerized system is needed to handle this in order to minimize these errors and also to optimize the results of reports from employee attendance. Rapid Application Development is one method in application development that is very suitable for developing digital applications at this time by emphasizing short development cycle and uses an object-oriented approach in its development system.